The origins of writing: A neurolinguistic perspective on written communication - Jiménez-Pérez, Elena del Pilar; García Guirao, Pedro (East European Journal of Psycholinguistics, 2023)
If homo sapiens, understood as the evolution of the current human being, was characterized by a cerebral advance and a much more evolved communicative capacity than its ancestors, then it is not conceivable that the origin of writing as the maximum exponent of homo sapiens’ need for communication did not improve until many thousands of years later. The fact that the first linguistic system perfected and agreed upon by an entire society dates from 3,500 years ago does not prove that this is the origin of writing. Writing, as the origin of the word itself indicates (both in Spanish and English), implies an attempt to communicate in writing and does not require a sophisticated and mature language with a developed grammar, phonetics, or semantics. No matter how rough, clumsy, crude, sparse, scanty, and incomprehensible these early written manifestations may have been, they are samples of writing. Taking into account this starting point, which is not new, the present study suggests a new classification of the origin of writing up to the present day. As long as no more ancient writing endeavors appear, the first attempts at written communication date back to about 40,000 years ago. From then until now, three periods have developed from the linguistic point of view: proto-writing, emergent writing, and maturity. These periods match the cognitive development of human beings with respect to their historical achievements of globalization.Disclosure StatementNo potential conflict of interest was reported by the authors.* Corresponding author: Pedro García Guirao, 0000-0001-6641-508X pedro.gg@um.es